2021
DOI: 10.1186/s12199-021-01033-0
|View full text |Cite
|
Sign up to set email alerts
|

Early life blood lead levels and asthma diagnosis at age 4–6 years

Abstract: The USA has a high burden of childhood asthma. Previous studies have observed associations between higher blood lead levels and greater hypersensitivity in children. The objective of the present study was to estimate the association between blood lead concentrations during early childhood and an asthma diagnosis between 48 and 72 months of age amongst a cohort with well-characterized blood lead concentrations. Blood lead concentrations were measured at 6, 12, 18, 24, 36, and 48 months of age in 222 children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The intricate relationships between these trace elements and blood pressure require more investigation to be completely understood. The incidence and development of cerebral blood vessels in the heart have been linked to an imbalance of metals including cobalt, zinc, copper, and magnesium, according to some studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intricate relationships between these trace elements and blood pressure require more investigation to be completely understood. The incidence and development of cerebral blood vessels in the heart have been linked to an imbalance of metals including cobalt, zinc, copper, and magnesium, according to some studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental pollutions due to industrial and economic activities have posed various health risks [1][2][3]. Per-and polyfluoroalkyl substances (PFASs) have been used since approximately the 1940s as water and oil repellents, aqueous film-forming foam as a fire extinguisher, and surfactants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies observed that asthma induced by heavy metals was triggered by the immune system, indicating that heavy metals have great inflammatory potential and immunomodulatory effects on individuals [ 27 , 28 ]. Many studies have reported the association between heavy metals (Pb, Cd, Hg and Mn) and asthma [ 24 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%